Implementasi Method Buzz Group Dalam Hasil Belajar Luring Akidah Akhlak di Kelas VIII MTs Miftahul Jannah Tanjung Pura - Satria Wiguna; Muhammad Arif Hidayat; Desi Winda Sari (Reslaj : Religion Education Social Laa Roiba Journal, 2019)
The background of the problem of this research is the lack of student learning outcomes, it is proven that many students of class VIII MTS Miftahul Jannah whose scores are below the KKM. The objectives of this research are: To find out the learning outcomes on the subjects of aqidah morality in class VIII MTS Miftahul Jannah before and after using the buzz group learning method, and To find out whether the buzz group learning method can improve student learning outcomes. The type of research chosen is classroom action research (CAR), so this research uses the first cycle model to the next cycle. The results of this study showed that the learning outcomes of class VIII MTS Miftahul Jannah students increased after learning Akidah Akhlak was carried out using the buzz group learning method. This is indicated by the increase in student learning outcomes, namely from 34 students in the first cycle of students who had a complete score of only 26 students or 76.74% and in the second cycle, students who completed 100%.